Web Information Systems Engineering - WISE 2011 and 2012 Workshops : Combined WISE 2011 and WISE 2012 Workshops, Sydney Australia, October 12-14, 2011 and Paphos, Cyprus, November 28-30, 2012, Revised Selected Papers - Huang, Guangyan; Huang, Zhisheng; Paik, Hye-Young; Sheng, Quan Z.; Haller, Armin (Lecture Notes in Computer Science, 2013)
This book constitutes the revised selected papers of the combined workshops on Web Information Systems Engineering, WISE 2011 and WISE 2012, held in Sydney, Australia, in October 2011 and in Paphos, Cyprus, in November 2012. The seven workshops of WISE 2011-2012 have reported the recent developments and advances in the contemporary topics in the related fields of: Advanced Reasoning Technology for e-Science (ART 2012), Cloud-Enabled Business Process Management (CeBPM 2012), Engineering in the Semantic Enterprise (ESE 2012), Social Web Analysis for Trend Detection (SoWeTrend 2012), Big Data and Cloud (BDC 2012), Personalization in Cloud and Service Computing (PC-S 2011), and User-Focused Service Engineering, Consumption and Aggregation (USECA 2011).